1999
DOI: 10.1002/(sici)1097-461x(1999)75:4/5<543::aid-qua19>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting currents from molecular theory

Abstract: The gauge‐invariant method of London is used to solve the molecular orbital (MO) equations in a square planar slab, with one electron per site, in a perpendicular magnetic field. Pair currents appear because of the degeneracy and incomplete filling of highest occupied molecular orbital (HOMO). This type of electronic structure may alternatively result in an antiferromagnetic (AF) state or a charge density wave (CDW) state. The CDW state has alternating oxidation states which are different in two units, for exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Density functional theory calculations showed that the organic superconductor [BETS] 2 GaCl 4 has a non-uniform electronic structure at the Fermi surface with half-filled orbitals, as generally found for type II superconductors [29][30][31][32]. The half-filled orbitals couple to local open-shell singlet states creating available sites for two excess electrons to form the Cooper pair.…”
Section: Discussionmentioning
confidence: 99%
“…Density functional theory calculations showed that the organic superconductor [BETS] 2 GaCl 4 has a non-uniform electronic structure at the Fermi surface with half-filled orbitals, as generally found for type II superconductors [29][30][31][32]. The half-filled orbitals couple to local open-shell singlet states creating available sites for two excess electrons to form the Cooper pair.…”
Section: Discussionmentioning
confidence: 99%
“…SC currents are possible, if the intervening electron system [Cu­(II)­Cu­(II)] interacts with the precurser state and the successor state. , Since we know that there is a phase transfer from antiferromagnetic to charge alternant we know that Cu­(I)­Cu­(III) at one moment has the same energy as Cu­(II)­Cu­(II) (Figure ). The possibility for electron pair transfer with D = 0 is an experimental fact. , Doping is capable of changing the relative order in free energies of spin ordered and charged state in local mixed-valence systems.…”
Section: Disproportionation Charge Transfer (Dct) Pairing Pseudogapmentioning
confidence: 99%
“…The aim of the present paper is to consider pairing from a localized (or correlated) point of view, ,, when it converges to an intinerant behavior. Cuprates but not vanadates may become SC, even if U is about the same (2 eV).…”
Section: Introductionmentioning
confidence: 99%
“…2 States and orbital occupancy in the three possible states. Wave functions in parenthesis orbitals, interact with (ab + ba) to form the superconducting ground state [33,34]. Polarization by the alkali ions (not shown) makes the system stable, but does not affect the relative energy levels very much.…”
Section: Wave Functionsmentioning
confidence: 99%